O impacto dos determinantes da inovação na geração de ideias no Ensino Superior: a perceção dos estudantes como evidência - Correia, Pedro Miguel Alves Ribeiro; Mendes, Ireneu de Oliveira (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2018)
Higher Education Institutions (HEI) have faced in recent years several factors that limit the accomplishment of their missions, which has led them to focus on their capacity to create what constitutes something new. Innovation is often regarded as one of the main drivers of organizational success, being relatively recent its study in the public sector. The article aims to assess the importance of innovation in public HEIs, based on the analysis of students’ perceptions of higher education in Portugal. A theoretical framework on innovation in the public sector is presented, followed by a reference to the methodology used and the results achieved, ending with the study’s findings.